2003
DOI: 10.1074/jbc.m306998200
|View full text |Cite
|
Sign up to set email alerts
|

Schizosaccharomyces pombe Cells Deficient in Triacylglycerols Synthesis Undergo Apoptosis upon Entry into the Stationary Phase

Abstract: Triacylglycerols (TAG) are important energy storage molecules for nearly all eukaryotic organisms. In this study, we found that two gene products (Plh1p and Dga1p) are responsible for the terminal step of TAG synthesis in the fission yeast Schizosaccharomyces pombe through two different mechanisms: Plh1p is a phospholipid diacylglycerol acyltransferase, whereas Dga1p is an acyl-CoA:diacylglycerol acyltransferase. Cells with both dga1؉ and plh1 ؉ deleted (DKO cells) lost viability upon entry into the stationary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
132
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(137 citation statements)
references
References 53 publications
5
132
0
Order By: Relevance
“…1J Inset) also became deformed. Unexpectedly, the intranuclear vesicle-like structures may be lipid containing, as they were stained by Nile red that was used to reveal lipid droplets (storage particles) normally present in cytoplasm (19) (Fig. S3).…”
Section: Resultsmentioning
confidence: 99%
“…1J Inset) also became deformed. Unexpectedly, the intranuclear vesicle-like structures may be lipid containing, as they were stained by Nile red that was used to reveal lipid droplets (storage particles) normally present in cytoplasm (19) (Fig. S3).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, HDACs themselves are not involved in neutral lipid metabolism directly and SIR2 stimulates the accumulation of neutral lipids when cells were cultured with VPA. Recently, Zhang et al [26] reported that cells defective in TAG synthesis undergo apoptosis upon entry into the stationary phase and diacylglycerol (DAG) mediates fatty acid-induced lipoapoptosis in Schizosaccharomyces pombe. In our experiment, however, DAG and monoacylglycerol (MAG) levels of the cells cultured with or without VPA were quite low compared to TAG level analyzed by the TLC method.…”
Section: Discussionmentioning
confidence: 99%
“…several organisms (3,46) and is likely to play a major role in the metabolic syndrome of obesity, diabetes, and atherosclerosis. We therefore investigated the mechanism of cell death in yeast acyltransferase mutants treated with oleate or palmitoleate (Fig.…”
Section: Expression Of Human Dgat2mentioning
confidence: 99%